2009
DOI: 10.1063/1.3155800
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric transport properties of highly oriented FeSb2 thin films

Abstract: Highly textured FeSb 2 films were produced on quartz wafers by a sputtering method. Their resistivity and Seebeck coefficient ͑S͒ were measured and a maximum absolute value of S ϳ 160 V K −1 at 50 K was obtained. Hall measurements were employed to study the charge carrier concentrations and Hall mobilities of the FeSb 2 films. By comparing with the transport properties of FeSb 2 single crystals and an extrinsically doped FeSb 1.98 Te 0.02 single crystal, the thermoelectric properties of the FeSb 2 films are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…[27] Studies on oriented FeSb 2 thin films revealed similar suppression of S max due to low mobility of charge carriers. [28][29][30] It was also observed previously that the position and magnitude of S max is very sensitive to doping and charge-carrier concentration for FeSb 2 single crystals [2] as well as for FeSi. [31] In addition, charge-carrier scattering due to an increased number of grain boundaries in the FeSb 2 nanocomposite may play a role in reducing the potential across the grains, thereby reducing the absolute value of S max .…”
Section: Resultssupporting
confidence: 58%
“…[27] Studies on oriented FeSb 2 thin films revealed similar suppression of S max due to low mobility of charge carriers. [28][29][30] It was also observed previously that the position and magnitude of S max is very sensitive to doping and charge-carrier concentration for FeSb 2 single crystals [2] as well as for FeSi. [31] In addition, charge-carrier scattering due to an increased number of grain boundaries in the FeSb 2 nanocomposite may play a role in reducing the potential across the grains, thereby reducing the absolute value of S max .…”
Section: Resultssupporting
confidence: 58%
“…A decrease in the Seebeck coefficient at low temperature in polycrystal [10], thin films [15] and arsenic-substituted FeSb 2 single crystals [8] was reported earlier.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetron sputtering system used for the growth of FeSb 2 films in this work has been described in detail elsewhere [19]. In short, FeSb 2 films were grown on quartz (0001) wafers by sputtering a specifically prepared compound target.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, highly <101>-oriented FeSb 2 films were produced by a sputtering method [19]. The FeSb 2 films were shown to exhibit the same intrinsic properties as bulk single crystals, but the obtained carrier concentrations were six orders of magnitude larger than in the single crystals leading to a large reduction in the peak thermopower value.…”
Section: Confidential: Not For Distribution Submitted To Iop Publishmentioning
confidence: 99%